ChemInform Abstract: Tuberostemonine O from the Roots of Stemona tuberosa. Issue 2 (January 2015) - Kil, Yun‐Seo; Han, Ah‐Reum; Seo, Eun Kyoung
Abstract isolation and structure elucidation of tuberostemonine O (I)